Integration of Monetary and Fiscal Policy of the Countries of the Visegrad Group - Stanislav Kappel; Jan Janků (Review of Economic Perspectives, 2014)
The aim of this paper is to evaluate mutual interaction of monetary and fiscal policies in the countries of the Visegrad group, i.e. in the Czech Republic, Slovakia, Poland and Hungary. The relationship of monetary and fiscal policy - their coordination, cooperation or mutual antagonism - are basic determinants of successful implementation for economic policy of the state. Fiscal and monetary policies usually have different aims, and some conflict situations may arise in practical economic and political decision- making. Each policy has to make its decision with regard to the other one. Methodical approaches of this contribution are based on the game theory, which deals with the analysis of a wide range of decision situations with more participants (players) and it is primarily focused on the conflict situations. This game-theoretical approach is responsible for creating the theoretical model which is then dealt with in the empirical analysis. We find a distinctly stabilizing role of monetary policy and relatively problematic stabilizing role of fiscal policy in the analyzed countries. The dominant role of monetary policy is statistically confirmed in the case of the Czech Republic and Hungary.
Keywords: 330